ChemInform Abstract: C—C Coupling Through Intramolecular Dual C—H Activation Directed by a Removable Carboxylate Group: A Method for the Synthesis of Fluorenones under Mild Reaction Conditions. Issue 48 (2nd December 2014) - Liu, Lu; Wang, Fang; Li, Zhenghong; Wang, Jianhui
Abstract The Pd‐catalyzed intramolecular oxidative coupling of diphenylacetic acids affords fluorenones.